Integrated Approach: Synthesis, in vitro Evaluation and Computational Analysis of Bromoanilines as Potential Antioxidants - Longkumer, Naruti; Richa, Kikoleho; Karmaker, Rituparna; Singha, Basanta; Ahmed, Benzir; Longkumer, Penlisola; Gogoi, Partha Pratim; Boruah, Nichan; Barman, Rituraj; Bezbaruah, Bipul; et al. (Asian Journal of Chemistry, 2025)
Bromoanilines are pivotal in medicinal chemistry, serving as crucial intermediates for bioactive compounds like antioxidants and therapeutic agents. Despite their potential, their intrinsic properties remain underexplored. This study innovatively synthesized bioactive bromoanilines using a greener protocol with water as the solvent and cetyltrimethylammonium tribromide (CTMATB) as the brominating agent, chosen for its sustainable characteristics. The synthesized compounds were evaluated for their antioxidant activity using DPPH, where 4-bromo-2-nitroaniline (3a) demonstrated exceptional activity with an IC50 of 1.73 mg/mL, surpassing Trolox as a positive control. FRAP assay further validated the superior antioxidant behaviour of compound 3a. In-depth analysis via density functional theory (DFT) highlighted antioxidant mechanisms, favouring the sequential proton loss electron transfer (SPLET) pathway. Molecular docking with myeloperoxidase (MPO) with PDB ID: 1DNU underscored 3a's strong affinity, with a Moldock score of -54.98 kcal/mol. Further analyses through visual molecular dynamics (VMD), non-covalent interaction (NCI) and electron localization function (ELF), confirmed its stable interactions and electron distribution. Physico-chemical assessments underscored favourable drug-like profile and safety compound 3a. This comprehensive approach reveals 4-bromo-2-nitroaniline (3a) as a promising antioxidant with potential therapeutic applications. However, further studies including in vivo exploration and clinical trials are crucial to validate its efficacy and safety as an antioxidant.